KINERJA PENYULUH PERTANIAN LAPANGAN DALAM MELAKSANAKAN TUGAS POKOK PENYULUH DI BP3K KECAMATAN BANJAR BARU KABUPATEN TULANG BAWANG - Diqa Aulia Sari; Dewangga Nikmatullah; Serly Silviyanti S (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This research aims to determine the performance of agricultural extension worker in perfoming their main tasks and to know the factors that related with agricultural extension worker performance in implementing the main tasks on BP3K Banjar Baru Sub District.  This research is conducted by survey method in which location is selected purposively in Banjar Baru Sub District.  Respondents in this research are seven agricultural extension worker and 75 farmers.  The data is collected from January until February 2017 and analyzed by descriptive analysis and non-parametric statistics correlation Rank Spearman test for hypothesis verification.  The results of Hypothesis test showed that factors which related to agricultural extension worker’s performance were agricultural extension worker motivation level, income, and working facilities, whereas the factors that did not relate to performance of agricultural extension worker in implementing main tasks were total of their farmers target, reward system, and the distance of residence to the farmers target area (working area).  The result of this research showed that generally the performance of agricultural extension worker in implementing the main tasks of agricultural extension worker in BP3K Banjar Baru Sub District were in middle classification.Key words: agricultural extension worker, main tasks, performance